TANTANGAN DAN STRATEGI PENANGGULANGAN STUNTING DI DESA PAGUYUBAN - Susanti, Agus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stunting remains a significant public health challenge in rural areas, including Desa Paguyuban. This community service aimed to address stunting by distributing soy milk and informative brochures on proper nutrition and child care. The methodology involved direct engagement with the community through door-to-door visits and group sessions to ensure wide outreach. The results indicated increased awareness among mothers regarding the importance of balanced nutrition for their children. The distribution of soy milk, rich in protein and essential nutrients, supplemented the dietary needs of children at risk of stunting. The community showed positive reception towards the program, with many participants expressing commitment to improving their children's diets. The intervention's success highlights the effectiveness of combining nutritional support with educational initiatives in stunting prevention efforts